Theme of jealousy in fiction and philosophical works - Prostomolotov, Valerii; Prostomolotova, Alina (Psychiatry, Neurology and Medical Psychology, 2018)
The theme of jealousy is widely represented in fiction in the form of certain episodes (dramatic, tragic, comic ones). Usually the theme of jealousy is simply called in this way by the writers, and further it acts as a psychogenic-stress factor of a neurotic reaction, but in some works jealousy is the main content of masterpieces. Noting the truthfulness of cases in fiction, Leongard wrote: “Great writers are also great psychologists.” Taking into account the opinion of the classic psychology, a clinical and psychological analysis of two characters suffering from pathological jealousy was performed: Othello from the same drama by William Shakespeare and Pozdnyshev from L. Tolstoy’s novel “Kreutzer Sonata. Simultaneously, based on the materials of the Yasnaya Polyana notes D. Makovitsky, a physician of the Tolstoy family, a clinical and psychological analysis of the personality of the great writer and enlightener suffering from pathological jealousy was carried out.